FREQUENCY OF THORACIC SPINE STIFFNESS AND ITS ASSOCIATION WITH MUSCULOSKELETAL PAINS AT REHMAN MEDICAL INSTITUTE PESHAWAR: A CROSS-SECTIONAL STUDY - Khan, Bilal; Anees, Madiha; Bibi, Memoona; Sahibzada, Abdul Haseeb; Kifayat, Mariyam; Nayab, Rehana (Annals of Allied Health Sciences, 2025)
Objective: To determine the frequency of thoracic spine stiffness and its association with musculoskeletal pains. Material & Methods: A cross-sectional study was conducted on patients with musculoskeletal disorders visiting the physical therapy department of the Rehman Medical Institute for the period of August to December 2023. 73 participants were recruited through convenience sampling techniques. The participants were assessed through physical examination test, Nordic questionnaire and Numeric Pain Rating Scale. SPSS version 22 was used for analysis. Results: Most of the participants (42.5%) were in the age group of 26-40 years from which 58.9% of participants were male and 58.9% participants had a healthy BMI. Majority of them were office workers and 47.9% of them had back pain. Neck pain was experienced by 20.5% of the participants, lower limb pain by 17.8% and upper limb pain by 13.7% of the participants. Majority of the participants had rounded shoulders 46.6%, and 58.9% presented back dysfunction. Most of the participants had upper thoracic spine stiffness (38.4%). Conclusion: The current study concludes that there is no association between thoracic Spine stiffness and musculoskeletal disorders. However, there was a high frequency of Thoracic Spine stiffness in individuals with Musculoskeletal disorders.